Benefits of interactive lightings in landscape architecture - Hj. Baharuddin, Zainul Mukrim; Amir Hamzah, Nor Afizah (2016)
The issue of public space not fully utilized at night time and high crime rate due to lack of adequate lighting had bring fear to urban residents and low aesthetic values toward public spaces at night time . The paper discuss on elements of interactive lightings, the application of interactive lighting that can enhance landscape elements through hardscape and softscape elements that will contributing to beautification of night scenery at public areas. The aim of the paper is to examine the benefits of interactive lighting in landscape that can enhance the environment. At same time give information of the element of interactive lightings and elements of landscape architecture that can transform a dull public space into a lively attraction area especially parks, plaza and squares at night time by application of interactive lighting elements by utilization of landscape elements. The main objectives of research are to exploring interactive lighting benefits as good interactive lighting design in spaces creates various activities, especially passive and leisure activities which create good advantages to our health, social cohesion and feeling connection with natural environment with adequate lighting in public places. The research was conducted at I-city Shah Alam, a digital city that utilize interactive lighting as it focal attraction to welcoming visitors into the park. The research uses a quantitative and qualitative approach that consists of questionnaire survey, observation, interview and taking photograph. The result shows that the combination of interactive lighting elements and landscape elements are important to contributing betterment of environment, society and maximization of space Keywords: (interactive lighting elements, landscape elements, public spaces, users, experience)